Determination of the Optimum Conditions for Removal of Congo Red Dye by Peroxidase Enzyme Plant - Ridha, Aula. I.; J. M-Ridha, Mohanad (Al-Khwarizmi Engineering Journal, 2023)
The pollution producing from textile industries effluents is growing since the years, due to at discharged lots of it in water without treatment. The resulting effluent is colourful, highly toxic, and poses a significant environmental hazard. This problem can be solved by using enzymic biological treatment, where the Congo red dye was used with concentrations (100,200,300,500) mg /L, pH values (3,4,5,6,7,8), and variable temperatures (25,35,45)°C, the best removal of Congo red (CR) dye  under optimum conditions for degradation was at  concentration of 100 mg/L, at (pH 6, 25 °C) with efficiency of 99.85 % using the peroxidase enzyme extracted from red radish plant, while the removal percentage decreased when increase dye concentration .